Determination Of Total Flavonoid Content And Total Phenolic Content Of Pitanak Fruit Skin Extracts (Nephelium sp.) - Rina Saputri; Ali Rakhman Hakim (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
The search for the presence of flavonoid and phenolic compounds from plants is still being carried out. This is done because flavonoid and phenolic compounds have high potential as antioxidants. Pitanak fruit is a native fruit of Kalimantan and currently there is no research report on the content of flavonoid and phenolic compounds. This study aims to determine the total flavonoid content and total phenolic content of the pitanak fruit peel extract. This research is a quantitative research with descriptive observational design. The assay used the uv-vis spectrophotometer method. The secondary metabolite compounds contained in the pitanak fruit peel extract are alkaloids, flavonoids, tannins, terpenoids, steroids, and phenolics. Total flavonoid content is 33,183 ppm and total phenolic content is 126,88 ppm. The conclusion of this research is that the pitanak fruit peel extract has total flavonoid and phenolic levels which can be optimized as a source of medicinal raw materials.